Dialog Asal dan Lokal dalam Sistem Ketatanegaraan Islam - Ade Aam Khoeruman (Jurnal Iman dan Spiritualitas, 2021)
Some of the government systems that we know include theocracy, autocracy, monarchy, and democracy. Considering the principles of Islamic teachings above, the most appropriate is a democratic system, although not all follow Islamic instructions. Democracy holds absolute power in the people, while in Islam this is not the case. The Indonesian people have a democracy that is different from western democracies. This is because Indonesia adheres to a democracy that believes in the one and only God, i.e., Pancasila.